Antibiotic Prescription Practice of Dental Practitioners in a Public Sector Institute of Karachi - Sohail Saadat; Sidra Mohiuddin; Ambrina Qureshi (Journal of the Dow University of Health Sciences, 2013)
There are very few conditions in dentistry in which systemic antibiotics are indicated, as majority of dental diseases are managed by oral hygiene measures and local interventions. In contrast to it, inadequate antibiotic prescription practice of dentists is evident in literature. The objective of the study was to assess the antibiotic prescription practice of dentists employed in a public sector teaching institute of Karachi. It was a cross sectional study. Subjects and Methods: A cohort of dentists working in a public sector dental institute of Karachi was included in the study. A self-administered semi-structured validated questionnaire was utilized for assessing the antibiotic prescription practice. The data was entered and analyzed using statistical package for social science [SPSS] version 16.0. Results: The questionnaire was distributed to 110 dentists and 89 filled questionnaires were received back from the respondents, thus giving a response rate of 81%. Amoxicillin was the antibiotic of choice among 43.3%, Amoxicillin Clavulinate in 34% and Metronidazole in 11.3% of surveyed dentists for the treatment of acute dental infections in patients without any known allergy; whereas Erythromycin (22.5%), Cephalaxin (23.6%) and Clindamycin (30.30%) was preferred for patients allergic to penicillin. Majority of respondents prescribe antibiotics for cellulitis (85.39%), pericronitis (75.20%), acute necrotizing ulcerative gingivitis (70.70%), periodontal abscess (65.10%), acute pulpitis (53.90%), chronic periodontitis (41.50%), chronic marginal gingivitis (24.70%) and dry socket (17.90%).